2018
DOI: 10.1021/acssuschemeng.8b01089
|View full text |Cite
|
Sign up to set email alerts
|

Functional Protein Concentrates Extracted from the Green Marine Macroalga Ulva sp., by High Voltage Pulsed Electric Fields and Mechanical Press

Abstract: With decreasing available land and fresh-water resources, the oceans become attractive alternatives for the production of valuable biomass, comparable to terrestrial crops. Seaweed cultivation for food, chemicals, and fuels is already under intensive development, yet efficient technologies for separation of major components are still missing. We report a food-grade process for the extraction of proteins from a green macroalga, Ulva sp., using high-voltage pulsed electric field (PEF) cell-membrane permeabilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 66 publications
4
40
4
Order By: Relevance
“…However, some authors believe that PEF has a good potential in integrated seaweed biorefinery approaches, particularly as a pretreatment to disrupt biomass and facilitate extraction using other complementary technologies [ 62 ]. Postma et al [ 84 ] studied PEF on the release of water-soluble carbohydrates and proteins from Ulva lactuca and obtained the yields of <15% and 15%, respectively and Robin et al [ 85 ] showed a 20% of protein yield from the same seaweed.…”
Section: Recovery Of Added-value Compoundsmentioning
confidence: 99%
“…However, some authors believe that PEF has a good potential in integrated seaweed biorefinery approaches, particularly as a pretreatment to disrupt biomass and facilitate extraction using other complementary technologies [ 62 ]. Postma et al [ 84 ] studied PEF on the release of water-soluble carbohydrates and proteins from Ulva lactuca and obtained the yields of <15% and 15%, respectively and Robin et al [ 85 ] showed a 20% of protein yield from the same seaweed.…”
Section: Recovery Of Added-value Compoundsmentioning
confidence: 99%
“…was chosen as the model species as it is very common on the shores of Israel and displayed high biomass productivity in extensive cultivation offshore in Israeli waters . Furthermore, the production of proteins and starch, and biomass fermentation to acetone, ethanol, butanol, and polyhydroxyalkanoates from several Ulva species has already been demonstrated …”
Section: Introductionmentioning
confidence: 99%
“…PEF coupled with mechanical pressing was employed for protein extraction from Ulva sp. An optimized protocol (see Table 2) resulted in a seven-fold increase in total protein yield (∼20% protein in the extract) when compared to an extract obtained using an osmotic shock [46]. Moreover, the PEF aided Ulva sp.…”
Section: Pulsed Electric Fieldmentioning
confidence: 99%